PENGARUH PERSEPSI RISIKO DAN PERSEPSI HARGA TERHADAP PERMINTAAN ONLINE SAYUR ORGANIK (Suatu Kasus di E-Grocery XYZ) - Evita, Beatrice; Pardian, Pandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Vegetables sold online make consumers unable to see and experience the organic vegetables directly, this causes consumers to be uncertain whether the product can meet their expectations. This shows that there is doubt to buy online, especially when buying agricultural products which can lead to a perceived risk,. If someone has a good perception of the price of a product, this can lead to a purchasing decision. The purpose of this study is to find out how the level of perceived risk and demand in E-Grocery XYZ and the effect of perceived risk and price perception on the demand for organic vegetables online in E-Grocery XYZ. This research was conducted with a quantitative design using survey research methods with simple random sampling techniques and utilizing SPSS 22 program assistance. The results showed that the level of perceived risk and demand felt by respondents was in the medium category related to purchasing organic vegetables at E-Grocery XYZ. Meanwhile, price perception is in the high category.. Perceived risk and price perception together have no effect on demand.